Doskonała teoria profesora Prognozy - Skalski, Tadeusz (Filozofia Nauki, 2003)
Professor Prognosis is a fictional character. His name - Prognosis - is meaningful and refers to a wonderful theory. Using his theory Professor is able to predict the behaviour of a human being with stunning accuracy; its predictive power is much greater than any other scientific theory. As for its predictive power the theory in question is so great that it seems impossible. We are inclined to think that it cannot be a theory. It must be something else. But what else could it be? The mystery has a simple solution. It turns out that the 'theory' applies only to one man and the man is Professor Prognosis himself. Now everything seems crystal clear. Professor Prognosis has deceived us. There is neither theory, nor predictions. As a matter of fact he does not predict but uses his power to control his behaviour. Every human being can do it. It is obvious. So what is the problem? The problem is that this solution is very traditional. It involves agency and free will. The main point of the paper was to make it look obvious.